Soft triboelectric nanogenerators for mechanical energy scavenging and self-powered sensors. (June 2021) - Song, Yiding; Wang, Nan; Hu, Chaosheng; Wang, Zhong Lin; Yang, Ya
Abstract: Efficient scavenging and converting energy from surrounding environment to achieve the self-powered operation of electronics has attracted tremendous interest to meet the energy needs of the rapidly growing Internet of Things and portable devices. As a promising technology, the triboelectric nanogenerator (TENG) possesses the capability of efficient utilization of ambient mechanical energy for energy supply and self-powered sensing. By integrating the soft materials into TENG, the soft TENG can be triggered by a quite weak external mechanical stimulation and realize a better conversion of micro mechanical energy. Meanwhile, the deformable soft TENGs further expand the application scenarios of TENGs. Here, the advances of soft TENGs by focusing on the fundamentals, candidate materials, promising structures, applications in energy scavenging and self-powered sensors are reviewed. In particular, the wearable and implantable soft TENGs, through which the related self-powered sensing or biomechanical energy harvesting can be realized in vivo and in vitro respectively, are summarized. Finally, the unique advantages and possible focuses for scientists in future of soft TENGs are emphasized. Graphical Abstract: Efficient scavenging and converting energy from surrounding environment to achieve the self-powered operation of electronics has attracted tremendous interest to meet the energy needs of the rapidly growing Internet of Things and portable devices. As a promising technology, the triboelectric nanogenerator (TENG) possesses the capability of efficient utilization of ambient mechanical energy for energy supply and self-powered sensing. By integrating the soft materials into TENG, the soft TENG can be triggered by a quite weak external mechanical stimulation and realize a better conversion of micro mechanical energy. Meanwhile, the deformable soft TENGs further expand the application scenarios of TENGs. Here, the advances of soft TENGs by focusing on the fundamentals, candidate materials, promising structures, applications in energy scavenging and self-powered sensors are reviewed. In particular, the wearable and implantable soft TENGs, through which the related self-powered sensing or biomechanical energy harvesting can be realized in vivo and in vitro respectively, are summarized. Finally, the unique advantages and possible focuses for scientists in future of soft TENGs are emphasized. ga1 Highlights: The recent progress and the applicability of soft TENGs in various applications are comprehensively summarized. By integrating the soft materials into TENG, the soft TENG can be triggered by a quite weak external mechanical stimulation. The unique advantages, the possible challenges and future research directions of soft TENGs are summarized.